Critical thinking skills : developing effective analysis and argument - Cottrell, Stella (Basingstoke : Palgrave MacMillan, 2011)
What is critical thinking? -- How well do you think? : Develop your thinking skills -- What's their point? : Identifying arguments -- Is it an argument? : Argument and non-argument -- How well do they say it? : Clarity, consistency and structure -- Reading between the lines: recognising underlying assumptions and implicit arguments -- Does it add up? : Identifying flaws in the argument -- Where's the proof? : Finding and evaluating sources of evidence -- Critical reading and note-making: critical selection, interpretation and noting of source material -- Critical, analytical writing: critical thinking when writing -- Where's the analysis? : Evaluating critical writing -- Critical reflection.
Includes bibliographical references (p. 278-279) and index.
Keywords: Critical thinking; Critical thinking -- Study and teaching; Study skills